KAJIAN PEMBUATAN MASKER WAJAH ORGANIK DARI CAMPURAN AMPAS KOPI, AMPAS TEH HIJAU, KUNYIT, DAN TEPUNG BERAS - Mohammad Fuad fauzul mu'tamar (Agroindustrial Technology Journal, 2022)
The coffea sp plant, commonly known as the coffee plant, is one of the most common plants found in the highlands. As a result of the trend to drink coffee, the juice and leftover commissary always end up as waste. The research was intended to exploit coffee dregs that we were not aware of were still good enough for the face to make into a facial mask. Masks are made using a different method of mixing coffee residue 50%, rice 20%, turmeric 20% and 10 percent green tea powder. The coffee grounds are roasted first for 15 minutes and then mashed through a blender. The turmeric is thin and dried in the sun until it is roasted for 15 minutes and then smoothed through a blender.Green tea here USES green tea powder so there's no need for subtlety. All the coffee residue, saffron and the green mixed into one was then sifted to make the masks produced completely smooth. Tests made for this study were the ph test, the age-old trial, and the organoleptic test. The result of this study is an average of 6,5 on the organoleptic test where the panelis is quite partial to the facial products of the coffee grounds. Results from the ph test came to 7,1 where this figure is still a reasonable measure for facial skin. Results from the old time-tested dry period obtained increased 11 minutes. The facial masks of the coffee grounds are well received and are competing in the marketplace